2021
DOI: 10.1542/hpeds.2020-002659
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Pediatric Rapid Response Systems: Results From a Survey of PRIS Hospitals

Abstract: BACKGROUND: Many hospitals use rapid response systems (RRSs) to identify and intervene on hospitalized children at risk for deterioration. OBJECTIVES: To describe RRS characteristics across hospitals in the Pediatric Research in Inpatient Settings (PRIS) network. METHODS: We developed the survey through a series of prospective respondent, expert, and cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…[33][34][35][36][37] Furthermore, sepsis (105/471, 22.30%) is the second most prevalent cause, with a higher incidence reported by White K, Scott IA, and other s co-workers (2016) at 29.5%, %, [38] a lower rate than ours at 16.1%, [33] and a higher incidence reported by Lockwood JM, Ziniel SI, and Bona de CP (2021) at 44%. [39] The pediatric rapid response team is an excellent tool for initiating early goal-directed therapy for sepsis and lowering sepsis-related mortality. [40] Crossing the Quality Chasm, a 2001 publication, encourages healthcare professionals and policymakers to implement new system methodologies and ideas to accomplish change.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] Furthermore, sepsis (105/471, 22.30%) is the second most prevalent cause, with a higher incidence reported by White K, Scott IA, and other s co-workers (2016) at 29.5%, %, [38] a lower rate than ours at 16.1%, [33] and a higher incidence reported by Lockwood JM, Ziniel SI, and Bona de CP (2021) at 44%. [39] The pediatric rapid response team is an excellent tool for initiating early goal-directed therapy for sepsis and lowering sepsis-related mortality. [40] Crossing the Quality Chasm, a 2001 publication, encourages healthcare professionals and policymakers to implement new system methodologies and ideas to accomplish change.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, only three studies (Martinez et al, 2018;Meulmester et al, 2018Meulmester et al, , 2021 directly measured the RRT triggers. The remaining five studies (Jayaram et al, 2017;Kolovos et al, 2018;Kun et al, 2019;Lockwood et al, 2021;McKelvie et al, 2017) reported on triggers as their secondary outcomes.…”
Section: Pediatric Triggersmentioning
confidence: 99%
“…Finally, proactive surveillance teams, while relatively uncommon in the United States, represent another strategy to enhance the afferent arm of the RRS 8 . Comprised variably of staff from the intensive care unit (ICU) or the ward, surveillance teams—which may be multidisciplinary—are designed to augment the resources of the ward team in promoting early recognition of clinical deterioration 8 . However, the impact of this care model on patient outcomes is not yet known.…”
Section: Rapid Response Systems (Rrss)mentioning
confidence: 99%
“…8 Comprised variably of staff from the intensive care unit (ICU) or the ward, surveillance teams-which may be multidisciplinary-are designed to augment the resources of the ward team in promoting early recognition of clinical deterioration. 8 However, the impact of this care model on patient outcomes is not yet known. Active innovation in the electronic health record and embedded software applications focuses on dashboards and data visualizations showing risk status (e.g., "watcher" activations) or trends in PEWS.…”
Section: Afferent Arm: Deterioration Prediction and Detectionmentioning
confidence: 99%